Outsourcing in Malaysian healthcare support services: A study on the causes of increased operational costs - Mustapa, Fara Diva; Mustapa, Muzani; Ismail, Fuziah; Ali, Kherun Nita (2006)
This paper explores the causes of the significant increase in the Malaysian Ministry of Health (MoH) healthcare support sevices. The issue was derived from the drawbacks of outsourcing which surfaces from the transaction costs. Coupled with the benefits to the host organisation are the drawbacks namely the information costs, negotiating and bargaining, and the costs of policing and enforcement. It later affects the outsourcing process and requires additional spending to the client. The findings showed that the bounded rationality, opportunism and the asset specificity are the main reasons for the existence of the three. Another contributing factor that led to the increment is was the broad scope of the outsourcing implemented by MoH for an extension of 15 years. It exposed the private service provider to uncertainty that later created a risk averse behaviour particularly on their pricing.